Pensar a cibercultura ambientalista: comunicação, mobilização e as estratégias discursivas do Greenpeace Brasil - Miguel, Katarini Giroldo (2014)
Our thesis postulates the existence of an environmental cyberculture, typical of the environmental movement, which has a communicative dynamics characterized by discourse strategies and specific mobilization. The environmental movement, represented here by the international organization Greenpeace, knew how to appropriate the digital tools, to spread the problematic in a scenario of digital social networks, cyberactivism, interactivity and the composition of a networked public sphere, that we put into debate. To understand this situation, we performed an extensive theoretical discussion, in constant dialogue with our object of study, covering the history of the environmentalism and its place as a social movement; the technologies of sociability, the Internet and its media as a space of resistance and control, noting the cyberculture as the contemporary culture itself, guided by technological influences. We conducted interviews with volunteers, followers and people in charge of the communication of Greenpeace, that allowed us to trace the motivations of participation and to confirm that the engagement in the environmental cause was strongly driven by the easiness of cyberspace. The discursive strategies have been elucidated with the methodological coordinates of Discourse Analysis, focused on identifying the ethos and the scenes of enunciation, based on an analysis protocol we formulated to understand the way of saying that leads subjects to adhere massively to the environmental discourse. In the first step of the analysis, we performed a diagnosis of quantitative perspective and exploratory aspect to discriminate the campaigns/main themes and assess the impact of the issues in digital social networks and the mainstream media. Subsequently, we selected the texts of the main campaigns that have passed through the qualitative phase, which encompassed lexical items, argumentative techniques and elements of contrast, as well as external aspects to the linguistic text, such as photos, videos, colors and predominant scenes. The discourse on environmental cyberculture unveils the ethos of the friend and the partner, ranging from drama and aggression to bring attention to the cause. Serious environmental problems such as environmental complaints are dealt as a playful ethos, even childish, using colloquial language and codes of the contemporary culture – cartoons, virtual games, beautiful animals that sing and dance – that before our eyes reveal a schizophrenic scenography, but is precisely what ensures the success of the campaigns.(AU)